Separation membrane, its manufacturing method and use
By introducing self-assembled crosslinked polyphenols and polyamine modified layers into the separation membrane, the problem of low separation efficiency of magnesium lithium in the prior art is solved, and the effect of efficient separation and high water flux is achieved.
Patent Information
- Application Number
- JP2024564562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-05-19
AI Technical Summary
Existing commercially leverable nanofiltration membranes are inefficient when separating magnesium and lithium, and the separation coefficient is usually less than 5, making it impossible to effectively extract lithium resources from salt lakes.
A separation membrane consisting of a base layer, a pore support layer, a polyamide layer and a modified layer is used. The modified layer is composed of crosslinked polyphenols and polyamine units, and is formed on the polyamide layer through self-assembly reaction. The pore size of the modified layer is between 0.1 and 0.5 nanometers and the surface zeta potential is between -5 and 30 millivolts.
It achieves efficient blocking of magnesium ions, improves the separation efficiency of magnesium lithium, and maintains high water flux and high processing efficiency.
Smart Images

Figure 2025514445000001_ABST
Abstract
Description
Detailed Description of the Invention
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of Chinese Application No. 202210555981.0, filed on May 20, 2022, the contents of which are incorporated herein by reference.
[0002] [Technical field] The present invention relates to the field of membranes, in particular to separation membranes, their production methods and uses.
[0003] [Background technology] With the popularity of new energy vehicles, the demand for lithium energy is gradually increasing. In China, most of the lithium resources are contained in the salt water of salt lakes. In addition to lithium ions, the water of salt lakes also contains a lot of magnesium ions and sodium ions, making it technically difficult to extract pure lithium resources from salt lakes. Researchers have developed a series of methods and processes to obtain lithium resources, including precipitation, solar pond method, extraction method, calcination method, membrane separation method, and adsorption method. Among them, membrane separation and adsorption methods have been most widely studied.
[0004] However, existing commercially available nanofiltration membranes are not designed to separate magnesium and lithium, and the separation efficiency of magnesium ions and lithium ions is very low, with a magnesium-lithium separation factor usually less than 5, making them unusable for the extraction of lithium from salt lakes. Therefore, how to achieve efficient separation of magnesium and lithium still faces many challenges.
[0005] [Summary of the invention] [Problem to be solved by the invention] In order to solve the above problems in the prior art, the object of the present invention is to provide a separation membrane having a high density and a high surface electrode potential (Zeta potential), which can effectively block magnesium ions when used for separating magnesium and lithium, thereby achieving a high magnesium-lithium separation efficiency, and which has a large water permeability and a high treatment efficiency, as well as a manufacturing method and use thereof.
[0006] [Means for solving the problem] In order to achieve the above object, the first aspect of the present invention comprises: The substrate includes a substrate layer, a porous support layer, a polyamide layer, and a modification layer, in that order; The crosslinked polymer forming the modification layer comprises structural units derived from polyphenols and structural units derived from polyamines, at least a portion of the structural units derived from polyphenols are also connected to the polyamide layer through the ortho positions of the phenolic hydroxyl groups; A separation membrane is provided having a pore size of 0.1 to 0.5 nm and a surface Zeta potential of -5 mV to 30 mV.
[0007] A second aspect of the present invention is Producing a porous support layer, a polyamide layer, and a modification layer in this order on a substrate layer; The present invention provides a method for producing a separation membrane, the method comprising: performing a first contact of a polyamide layer side of a material including a substrate layer, a porous support layer, and a polyamide layer with the polyphenol solution while flowing the polyphenol solution under a first pressure; and performing a second contact of a polyamide layer side of the material with the polyamine solution while flowing the polyamine solution under a second pressure, thereby completing a self-assembly reaction.
[0008] A third aspect of the present invention provides a separation membrane produced by the above-described method.
[0009] A fourth aspect of the present invention provides the use of a separation membrane according to the first or third aspect in the separation of magnesium and lithium.
[0010] [Effects of the invention] The separation membrane according to the present invention has a high density and a high surface electrode potential (Zeta potential), and when used for separating magnesium and lithium, it can effectively block magnesium ions and allows lithium ions to pass as much as possible, thereby achieving high magnesium-lithium separation efficiency, and also has a large water permeability and high treatment efficiency.
[0011] In the method for producing a separation membrane according to the present invention, a polyamine solution and a polyphenol solution are flowed under a first pressure and a second pressure, while a self-assembly reaction of polyamine and polyphenol is carried out on a polyamide layer to obtain a separation membrane including a modified layer. The separation membrane produced thereby has a high density and a high surface electrode potential (Zeta potential), and when used for separating magnesium and lithium, it can effectively block magnesium ions and pass lithium ions as much as possible, thereby achieving a high magnesium-lithium separation efficiency, a large water passing amount, and a high treatment efficiency. Furthermore, the production method has a simple process and is expected to be industrialized.
[0012] [Brief description of the drawings] FIG. 1 shows infrared spectra of the separation membranes produced in Example 1 and Comparative Examples 1 and 2 of the present invention. [Figure 2] A curve showing the change in surface Zeta potential of a separation membrane with the number of self-assembly cycles. [Figure 3] A curve showing the change in surface Zeta potential of a separation membrane depending on the self-assembly pressure (first pressure / second pressure). [Figure 4] A curve showing the change in contact angle of a separation membrane depending on the self-assembly pressure (first pressure / second pressure). FIG. 5 is a curve showing the change in contact angle of a separation membrane depending on the number of times of self-assembly. 6A and 6B are cross-sectional SEM images of the separation membranes of Comparative Example 1 (FIG. 6A) and Example 10 (FIG. 6B). FIG. 7 is an XPS nitrogen element map of the separation membranes produced in Example 1 and Comparative Example 1.
[0013] [Mode for carrying out the invention] The endpoints of the ranges and any values disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. With respect to numerical ranges, the endpoints of each range, the endpoints of each range and the individual dot values, and the individual dot values can be combined to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] In a first aspect, the present invention provides a membrane comprising, in order, a substrate layer, a porous support layer, a polyamide layer, and a modification layer, The crosslinked polymer forming the modification layer comprises structural units derived from polyphenols and structural units derived from polyamines, at least a portion of the structural units derived from polyphenols are also connected to the polyamide layer through the ortho positions of the phenolic hydroxyl groups; A separation membrane is provided having a pore size of 0.1 to 0.5 nm and a surface Zeta potential of -5 mV to 30 mV.
[0015] As a result of research, the inventors have found that the separation membrane contains the above-mentioned modification layer, so that the pore size of the separation membrane can be in the range of the pore size described in the present invention, and the surface Zeta potential of the separation membrane can be in the range of the surface Zeta potential described in the present invention. The separation membrane has a high density and a high surface electrode potential, and when used to separate lithium and magnesium, it is easy to block divalent magnesium ions, makes it difficult for magnesium ions in liquid to pass through the separation membrane, and allows monovalent lithium ions to pass as much as possible, thereby achieving high magnesium-lithium separation efficiency. In addition, due to the cooperation of the above-mentioned multiple layers, the separation membrane has a large water permeability, and when used to separate magnesium and lithium in liquid, the treatment efficiency is improved.
[0016] In the present invention, the pore size of the separation membrane is measured by a polyethylene glycol (PEG) solute migration method, the detailed steps of which are as follows:
[0017] (1) Test the rejection rate of the separation membrane against PEG of various molecular sizes.
[0018] (2) Linear fitting is performed on the PEG size and rejection rate in a log-probability coordinate system, and the PEG size corresponding to 50% rejection rate is determined as the average pore size of the separation membrane.
[0019] In the present invention, the surface Zeta potential of the separation membrane is measured by a potential analyzer.
[0020] Furthermore, the separation membrane has a pore size of 0.15 to 0.3 nm and a surface Zeta potential of 1 mV to 10 mV.
[0021] According to the present invention, the modified layer comprises a structural unit as shown in formula I: [ka]
[0022] In the present invention, the inventors conducted research and tested the nitrogen element in the modified layer of the separation membrane by XPS. As a result, the modified layer of the separation membrane according to the present invention contains a structural unit represented by formula I, that is, the modified layer contains a π-π bond formed by a benzene ring-nitrogen atom-benzene ring. * It has been found that there exists an electronically conjugated structural unit. At least a part of the structural unit derived from polyphenol in the modified layer undergoes a crosslinking reaction with the structural unit derived from polyamine and / or the nitrogen atom derived from the polyamide layer through the ortho position of the phenolic hydroxyl group, thereby further reducing the pore size of the separation membrane containing the modified layer, further improving the density of the separation membrane, and further increasing the magnesium-lithium separation efficiency when the separation membrane is used for separating magnesium and lithium.
[0023] According to the present invention, the content of the structural unit derived from the polyphenol on the membrane surface is 2×10 -3 ~5×10 -2 mg / cm 2 The content of the polyamine-derived structural unit on the membrane surface is 1×10 -3~2.5×10 -2 mg / cm 2 is
[0024] In the present invention, the contents of polyphenol-derived structural units and polyamine-derived structural units on the membrane surface of the separation membrane are measured by the following steps.
[0025] The membrane including the substrate layer, the porous support layer, and the polyamide layer was dried in a vacuum oven at 60° C. for 24 hours, and then the mass of the membrane was weighed. n The membrane is placed in a membrane cell, a polyphenol aqueous solution of a predetermined concentration is placed in the supply tank, and cycled for a certain period of time under predetermined conditions. The membrane sheet is then removed, the surface of the membrane sheet is thoroughly washed with deionized water, and dried at 60°C for 24 hours. The mass of the membrane is then weighed and the mass is expressed as W n Next, the membrane is placed in a membrane cell, a polyamine aqueous solution of a specified concentration is added to the supply tank, and cycled for a certain period of time under specified conditions. The membrane sheet is then taken out, the surface of the membrane sheet is thoroughly washed with deionized water, and dried at 60°C for 24 h. The mass of the membrane is then weighed and N n (mg). Each time the separation membrane was modified, the polyphenol content on the membrane surface, P n and polyamine content T n are calculated by the following formulas, respectively:
number
[0026] Here, if n is greater than 1, then M n =N n-1 and for n=1, M n is the initial mass of the polyamide membrane sheet.
number
[0027] The total content of polyphenols on the surface of the separation membrane after self-assembly is ΣPn (n ≧ 1), and the total content of polyamines on the surface is ΣTn (n ≧ 1). where n is the number of self-assembly times and S is the effective membrane area (unit: cm 2 ).
[0028] In the present invention, the inventors have found through their research that when the content of the polyphenol-derived structural unit and the polyamine-derived structural unit on the membrane surface is within the above range, the separation membrane has an appropriate density and thickness, thereby ensuring a high magnesium-lithium separation factor and water permeability of the separation membrane.
[0029] Furthermore, the content of the structural unit derived from the polyphenol on the membrane surface is 2.5×10 -3 ~5×10 -2 mg / cm 2 The content of the polyamine-derived structural unit on the membrane surface is 4×10 -3 ~2×10 -2 mg / cm 2 It is.
[0030] According to the present invention, the content of N atoms in the modification layer is 13 to 20 at. %.
[0031] In the present invention, the content of N atoms in the modified layer is measured by an X-ray photoelectron spectrometer.
[0032] In the present invention, when the content of N atoms in the modified layer satisfies the above range, the separation membrane has a high surface electrode potential and excellent hydrophilicity, and when used for separating magnesium and lithium, it has a high magnesium-lithium separation efficiency and a large water permeation rate.
[0033] Furthermore, the content of N atoms in the modification layer is 13.5 to 18.5 at. %.
[0034] According to the present invention, the contact angle of the separation membrane is 20 to 60°.
[0035] In the present invention, the contact angle of the separation membrane is measured by the following method. A DSA100 surface contact angle measuring device manufactured by KRUSS, Germany, is used to measure the surface contact angle of the composite membrane sample using the sessile drop method. Before measurement, the sample is dried in a vacuum oven at 60°C for 30 minutes to remove moisture on its surface and inside, and then the dried membrane is attached to a flat glass slide with double-sided tape, the volume of each water drop during the test is 2 μL, and the test is performed immediately 3 s after the water drop is dropped on the membrane surface, and the average value of multiple measurements is obtained to determine the final contact angle.
[0036] In the present invention, it has been found that the separation membrane has a contact angle within the range described in the present invention, and therefore the separation membrane has excellent hydrophilicity and excellent water permeability.
[0037] Furthermore, the contact angle of the separation membrane is 20 to 40°.
[0038] According to the present invention, the separation membrane preferably has a thickness of 100 to 200 μm.
[0039] According to the present invention, the thickness of the substrate layer is preferably 30 to 150 μm, and more preferably 50 to 120 μm.
[0040] According to the invention, preferably, the thickness of said porous support layer is 10 to 100 μm, preferably 30 to 60 μm.
[0041] According to the invention, preferably the thickness of said polyamide layer is from 10 to 500 nm, preferably from 50 to 150 nm.
[0042] According to the present invention, the thickness of the modification layer is preferably from 1 to 200 nm, preferably from 10 to 60 nm.
[0043] In the present invention, the thicknesses of the separation membrane, the porous support layer and the polyamide layer are measured by a spiral micrometer and a scanning electron microscope, and the thickness of the modification layer is obtained by subtracting the thicknesses of the substrate layer, the porous support layer and the polyamide layer from the thickness of the separation membrane, where the thickness of the substrate layer is the thickness measured before applying the solution of the material of the porous support layer.
[0044] As a result of research, the inventors have found that within the above-mentioned thickness ranges of each layer, the above-mentioned layers work well together to provide the separation membrane with a small pore size and a high Zeta potential, and when used to separate magnesium and lithium, this separation membrane achieves both high magnesium-lithium separation efficiency and a large water permeability.
[0045] According to the present invention, the material of the base material layer is not particularly limited, but may be a material that is commonly used in the field, has a certain strength, is applicable to nanofiltration, reverse osmosis, etc., and performs a supporting function. Preferably, the material of the base material layer is at least one selected from polyester nonwoven fabric, polyethylene nonwoven fabric, and polypropylene nonwoven fabric.
[0046] According to the present invention, the material of the porous support layer is not particularly limited, but may be a material that is commonly used in the field and has a certain degree of supporting effect and forms a porous structure. More preferably, the material of the porous support layer is at least one selected from polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryletherketone. The porous structure in the porous support layer facilitates the passage of liquid. The number average molecular weight of the material of the porous support layer may be 50,000 to 100,000 g / mol.
[0047] According to the present invention, the polyamide layer is preferably synthesized from a polyamine and a polybasic acid chloride.
[0048] In the present invention, the polyamide layer has an appropriate crosslinked structure, and the amino compound contained therein can effectively block divalent magnesium ions.
[0049] Furthermore, the polyamine is at least one selected from polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine, and more preferably at least one of polyethyleneimine, piperazine, and polyethylenepolyamine.
[0050] Furthermore, the polybasic acid chloride is at least one selected from trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride, more preferably at least one of trimesoyl chloride and terephthaloyl chloride. When there are multiple types of polybasic acid chloride, they may be mixed in any ratio, and when the polybasic acid chloride is trimesoyl chloride and terephthaloyl chloride, the weight ratio of trimesoyl chloride to terephthaloyl chloride may be 1:1 to 10.
[0051] According to the invention, the modified layer is obtained by carrying out a self-assembly reaction of polyphenols and polyamines on a polyamide layer.
[0052] In the present invention, the self-assembly reaction includes a step of first contacting the polyamide layer side of a material including a base layer, a porous support layer, and a polyamide layer with a polyphenol solution while flowing the polyphenol solution under a first pressure, and then second contacting the polyamide layer side of the material with the polyamine solution while flowing the polyamine solution under a second pressure, thereby completing the self-assembly reaction.
[0053] According to the present invention, the polyphenol is one or more selected from tannic acid, tea polyphenols, gallic acid, catechin, lignin, sodium lignosulfonate, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin, and genistein, preferably tannic acid and / or tea polyphenols.
[0054] According to the present invention, the polyamine is at least one selected from polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
[0055] According to the present invention, the first pressure and the second pressure are each independently 0.1 to 1.2 MPa.
[0056] In the present invention, when the pressure applied when producing the modified layer satisfies the above range, the separation layer composed of both the modified layer and the polyamide layer has a high density, and the content of structural units derived from polyamine in the separation membrane is high, so that the hydrophilicity of the separation membrane is further increased, and finally, the separation membrane has excellent magnesium-lithium separation property and water permeability.
[0057] Furthermore, the first pressure and the second pressure are each independently 0.2 to 1 MPa.
[0058] In the present invention, the polyphenol solution and the polyamine solution are used in amounts such that the mass ratio of polyphenol to polyamine is 0.1 to 10:1.
[0059] In the present invention, when the mass ratio of polyphenol to polyamine satisfies the above range, sufficient reaction between polyphenol and polyamine is ensured, and the produced separation membrane is ensured to have the pore size required in the present invention. In addition, more amino groups remain on the surface of the separation membrane, and thus the separation membrane has the high surface Zeta potential and hydrophilicity required in the present invention. When the separation membrane is used to separate magnesium and lithium, it has a higher divalent magnesium ion rejection rate and a higher water permeability.
[0060] Furthermore, the polyphenol solution and the polyamine solution are used in amounts such that the mass ratio of polyphenol to polyamine is 0.2 to 6:1, preferably 0.5 to 6:1.
[0061] In the present invention, the concentration of the polyphenol solution is 0.00001 to 1 wt %, preferably 0.0001 to 0.1 wt %.
[0062] In the present invention, the concentration of the polyamine solution is 0.00001 to 1 wt %, and preferably 0.0001 to 0.1 wt %.
[0063] In the present invention, when the concentrations of the polyphenol solution and the polyamine solution are each independently within the above range, the produced separation membrane has the pore size, surface Zeta potential and thickness required in the present invention, and when used for separating magnesium and lithium, it increases the rejection rate for magnesium chloride and maintains good water permeability.
[0064] In the present invention, the temperature of the first contact and the second contact is independently 10 to 30°C.
[0065] In the present invention, when the temperature of the first contact and the second contact is within the above range, a sufficient reaction between polyphenol and polyamine is ensured, and the pore size and surface Zeta potential required in the present invention are imparted to the produced separation membrane, thereby improving the rejection rate of magnesium chloride and the separation efficiency of magnesium-lithium when the separation membrane is used for separating magnesium and lithium.
[0066] In the present invention, the time of the first contact in one self-assembly reaction is 1 to 120 minutes.
[0067] In the present invention, the time for the second contact in one self-assembly reaction is 1 to 120 minutes.
[0068] In the present invention, when the time of the first contact and the second contact in one self-assembly reaction satisfies the above range, not only is sufficient reaction between polyphenol and polyamine ensured, but also the density and thickness of the membrane separation layer composed of the polyamide layer and the modification layer are appropriately adjusted, and the separation membrane produced thereby has high water permeability and high magnesium-lithium separation ability.
[0069] Furthermore, in one self-assembly reaction, the time for the first contact is 10 to 60 minutes.
[0070] Furthermore, in one self-assembly reaction, the time for the second contact is 10 to 60 minutes.
[0071] In the present invention, the inventors have further studied and found that by repeating the following steps and performing self-assembly multiple times according to the method for producing a modified layer on the above-mentioned polyamide layer of a material including a base layer, a substrate layer, a porous support layer, and a polyamide layer, the separation membrane can have a high surface Zeta potential and a smaller pore size, and can further ensure high magnesium-lithium separation efficiency. Specifically, the number of times of the self-assembly reaction is 1 to 10 times, more preferably 2 to 5 times.
[0072] In one preferred embodiment of the present invention, the water permeability of the separation membrane is 20 L m -2 h -1 The MgCl2 rejection rate is 99% or more, and the magnesium-lithium separation factor is 70 or more.
[0073] In a more preferred embodiment of the present invention, the water permeability of the separation membrane is 20-40 L m -2 h-1 The MgCl2 rejection rate is 99% or more, and the magnesium-lithium separation factor is 100-250.
[0074] In a second aspect, the present invention provides a method for producing a porous support layer, a polyamide layer, and a modification layer, in that order, on a substrate layer, The present invention provides a method for producing a separation membrane, the method comprising: performing a first contact of a polyamide layer side of a material including a substrate layer, a porous support layer, and a polyamide layer with the polyphenol solution while flowing the polyphenol solution under a first pressure; and performing a second contact of a polyamide layer side of the material with the polyamine solution while flowing the polyamine solution under a second pressure, thereby completing a self-assembly reaction.
[0075] In the present invention, polyphenol and polyamine undergo a Michael addition reaction to form a crosslinked structure. The carbon atom at the ortho position of the carbon atom on the polyphenol on which the phenolic hydroxyl group exists reacts with the polyamine as a reaction site. When reacting on the surface of the polyamide layer, the carbon atom at the ortho position of the carbon atom on the polyphenol on which the phenolic hydroxyl group exists reacts with the amino in the polyamide layer as a reaction site.
[0076] In the present invention, a separation membrane is produced by the production method according to the second aspect of the present invention, that is, the polyphenol solution and the polyamine solution are flowed under a first pressure and a second pressure, and the polyamide layer side of a material including a substrate layer, a porous support layer, and a polyamide layer is contacted with the polyphenol solution and the polyamine solution in order to react. The polyphenol and the polyamine undergo a Michael addition reaction on the surface of the polyamide layer to form a crosslinked structure, and the carbon atom at the ortho position of the carbon atom on which a part of the phenolic hydroxyl group of the polyphenol exists may react with the amino in the polyamide layer and be connected to the polyamide layer.
[0077] In addition, when the polyphenol solution and the polyamine solution are allowed to flow under the action of the first and second pressures, the resulting separation membrane has a smaller pore size and a higher surface Zeta potential, i.e., the separation membrane according to the first aspect of the present invention is obtained. Specifically, in the present invention, the self-assembly reaction is carried out in a dynamic environment with a predetermined flow rate, thereby reducing the adsorption of polyphenols or polyamines to the membrane surface and increasing the amount of polyphenols or polyamines bound to the membrane surface through chemical bonds. As a result, the separation membrane undergoes self-assembly modification, which significantly improves the density and also has a high surface Zeta potential.
[0078] The separation membrane manufactured by the manufacturing method according to the second aspect of the present invention has a pore size within the pore size range described in the present invention and a surface Zeta potential within the surface Zeta potential range described in the present invention, and therefore the separation membrane has a high density and a high surface electrode potential, and when used to separate lithium and magnesium, it is easy to block divalent magnesium ions, makes it difficult for magnesium ions in liquid to pass through the separation membrane, and allows monovalent lithium ions to pass as much as possible, thereby achieving a high magnesium-lithium separation efficiency. In addition, due to the cooperation of the above-mentioned multiple layers, the separation membrane has a large water permeability, and when used to separate magnesium and lithium in liquid, the treatment efficiency is improved.
[0079] According to the present invention, the first pressure and the second pressure are each independently 0.1 to 1.2 MPa.
[0080] In the present invention, when the first pressure and the second pressure during the preparation of the modified layer are each independently within the above range, the polyphenol and the polyamine react more fully, and the prepared separation membrane has the pore size and surface Zeta potential required in the present invention, and when used for separating magnesium and lithium, the magnesium chloride rejection rate is high and the magnesium-lithium separation efficiency is excellent.
[0081] Furthermore, the first pressure and the second pressure are each independently 0.2 to 1 MPa.
[0082] In the present invention, the self-assembly reaction may be carried out in a cross-flow membrane cell, in which the cross-flow membrane cell circulates water into the membrane cell by a water pump to keep the water in the membrane cell in a flowing state, and pressure is applied by a pressure regulating valve, so that the first pressure and the second pressure of the manufacturing process are maintained to meet the requirements of the present invention.
[0083] In the present invention, the method for producing the modified layer can be carried out in a device commonly used in the field, such as a cross-flow membrane cell, and the method is simple in process and easy to industrialize.Here, when the self-assembly reaction is carried out in a cross-flow membrane cell, for example, after contacting the polyphenol with the material, the polyphenol solution is discharged, and the cross-flow membrane cell is repeatedly rinsed with deionized water to wash the polyphenol in the system and the polyphenol on the surface of the material.
[0084] In the present invention, in cross-flow membrane cell, the solution is continuously supplied to the cell by pump, so the total amount of polyphenol or polyamine in the solution generally exceeds the amount that can adhere to and react on the surface of membrane, thereby ensuring the modification layer required in the present invention.In the present invention, the flow rate of polyphenol solution and polyamine solution is not particularly limited, and when producing modification layer, it is sufficient that polyphenol solution and polyamine solution maintain a flowing state, and for example, the flow rate of the polyphenol solution or the polyamine solution can be 0.5-5L / min.
[0085] According to the present invention, the polyphenol solution and the polyamine solution are used in amounts such that the mass ratio of polyphenol to polyamine is 0.1 to 10:1.
[0086] In the present invention, when the mass ratio of polyphenol to polyamine satisfies the above range, sufficient reaction between polyphenol and polyamine is ensured, and the produced separation membrane is ensured to have the pore size required in the present invention. In addition, more amino groups remain on the surface of the separation membrane, and thus the separation membrane has the high surface Zeta potential and hydrophilicity required in the present invention. When the separation membrane is used to separate magnesium and lithium, it has a higher divalent magnesium ion rejection rate and a higher water permeability.
[0087] Furthermore, the polyphenol solution and the polyamine solution are used in amounts such that the mass ratio of polyphenol to polyamine is 0.2 to 6:1, preferably 0.5 to 6:1.
[0088] According to the present invention, the concentration of the polyphenol solution is 0.00001 to 1 wt %, preferably 0.0001 to 0.1 wt %.
[0089] According to the present invention, the concentration of the polyamine solution is 0.00001 to 1 wt %, preferably 0.0001 to 0.1 wt %.
[0090] In the present invention, when the concentrations of the polyphenol solution and the polyamine solution each independently satisfy the above ranges, the produced separation membrane has the pore size, surface Zeta potential and thickness required in the present invention, and when used for separating magnesium and lithium, it increases the rejection rate for magnesium chloride and maintains good water permeability.
[0091] According to the present invention, the temperature of the first contact and the second contact is independently 10 to 30°C.
[0092] In the present invention, when the temperature of the first contact and the second contact is within the above range, a sufficient reaction between polyphenol and polyamine is ensured, and the pore size and surface Zeta potential required in the present invention are imparted to the produced separation membrane, thereby improving the rejection rate of magnesium chloride and the separation efficiency of magnesium-lithium when the separation membrane is used for separating magnesium and lithium.
[0093] According to the present invention, the time of the first contact in one self-assembly reaction is 1 to 120 minutes.
[0094] According to the present invention, the time for the second contact in one self-assembly reaction is 1 to 120 minutes.
[0095] In the present invention, when the time of the first contact and the second contact in one self-assembly reaction satisfies the above range, not only is sufficient reaction between polyphenol and polyamine ensured, but also the density and thickness of the membrane separation layer composed of the polyamide layer and the modification layer are appropriately adjusted, and the separation membrane produced thereby has high water permeability and high magnesium-lithium separation ability.
[0096] Furthermore, in one self-assembly reaction, the time for the first contact is 10 to 60 minutes.
[0097] Furthermore, in one self-assembly reaction, the time for the second contact is 10 to 60 minutes.
[0098] In the present invention, the inventors have further studied and found that by repeating the following steps and performing self-assembly multiple times according to the method for producing a modified layer on the above-mentioned polyamide layer of a material including a base layer, a substrate layer, a porous support layer, and a polyamide layer, the separation membrane can have a high surface Zeta potential and a smaller pore size, and can further ensure high magnesium-lithium separation efficiency. Specifically, the number of times of the self-assembly reaction is 1 to 10 times, more preferably 2 to 5 times.
[0099] According to the present invention, the conditions for producing the modification layer include making the thickness of the modification layer in the separation membrane to be 1 to 200 nm, preferably 10 to 60 nm.
[0100] According to the present invention, the polyphenol in the polyphenol solution is one or more selected from tannic acid, tea polyphenols, gallic acid, catechin, lignin, sodium lignosulfonate, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin, and genistein, preferably tannic acid and / or tea polyphenols.
[0101] According to the present invention, the polyamine in the polyamine solution is at least one selected from polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
[0102] In the present invention, the method for producing a porous support layer on a substrate layer may be a method commonly used in the art.Preferably, the method for producing a porous support layer includes applying a solution containing a material for the porous support layer onto a substrate layer, and carrying out a phase transition to obtain a material containing the substrate layer and the porous support layer.
[0103] In the present invention, the specific coating method is not particularly limited, but may be a knife cord coating method.
[0104] According to the present invention, the conditions for the phase transition include immersion in water at 10 to 30° C. for 10 to 60 minutes.
[0105] In the present invention, when the method for producing the porous support layer is utilized, the solvent in the solution containing the material of the porous support layer gradually leaves the porous support layer when immersed in water, and such a phase transition further ensures that a support layer having a porous structure is obtained.
[0106] According to the present invention, the thickness of the base layer is preferably 30 to 150 μm, more preferably 50 to 120 μm. The thickness of the base layer is almost unchanged before and after the production.
[0107] In the present invention, the material of the base material layer is at least one selected from a polyester nonwoven fabric, a polyethylene nonwoven fabric, and a polypropylene nonwoven fabric.
[0108] According to the present invention, the conditions for producing the porous support layer preferably include setting the thickness of the porous support layer in the separation membrane to 10 to 100 μm, more preferably 30 to 60 μm. The thickness may be controlled by controlling the amount of coating, and since the thickness decreases after coating, there is a slight difference between the thickness set during coating and the thickness of the porous support layer of the finally obtained separation membrane. Usually, the thickness set during coating may be 40 to 60 μm higher than the desired porous support layer of the separation membrane.
[0109] According to the present invention, the concentration of the solution containing the material for the porous support layer is 10 to 20 wt %.
[0110] According to the present invention, the material of the porous support layer is at least one selected from polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryletherketone.
[0111] According to the present invention, the solvent in the solution containing the material of the porous support layer is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethylsulfoxide.
[0112] In the present invention, the method for producing the solution containing the material for the porous support layer is not particularly limited, and the solution may be produced by a method commonly used in the field. For example, the material for the porous support layer is first dissolved in a solvent and degassed (degassing is performed at 20 to 40°C for 10 to 180 minutes) to obtain a solution containing the material for the porous support layer.
[0113] In the present invention, preferably after the porous support layer is produced, the material is washed, for example by repeated water washing.
[0114] According to the present invention, the method for producing the polyamide layer includes the steps of contacting the surface of the porous support layer of a material including a substrate layer and a porous support layer with an aqueous phase containing a polyamine and an organic phase containing a polybasic acid chloride, in that order, and then performing a heat treatment.
[0115] In the present invention, according to the above method of contacting the aqueous phase containing polyamine and the organic phase containing polybasic acid chloride in order, the polyamide layer is obtained by interfacial polymerization. Such a polyamide layer has a crosslinked structure, is dense and thin, has high magnesium-lithium separation efficiency, and has a large water passing rate. Here, the contact with the aqueous phase and the organic phase may be performed at room temperature, for example, 23 to 28°C.
[0116] According to the present invention, the conditions for producing the polyamide layer include making the thickness of the polyamide layer in the separation membrane to be 10 to 500 nm, more preferably 50 to 300 nm.
[0117] According to the present invention, the time for which the porous support layer surface is contacted with the aqueous phase containing a polyamine is preferably 5 to 100 s, more preferably 10 to 60 s.
[0118] According to the present invention, the time for which the porous support layer surface is contacted with the organic phase containing the polybasic acid chloride is 10 to 200 s, more preferably 20 to 120 s.
[0119] According to the present invention, the aqueous phase containing the polyamine and the organic phase containing the polybasic acid chloride are used in amounts such that the mass ratio of polyamine to polybasic acid chloride is 0.1 to 10:1.
[0120] In addition, the present inventors have found that when the mass ratio of polyamine to polybasic acid chloride satisfies the above ratio, the produced polyamide layer has an appropriate pore size, and the polyamide layer has excellent lithium chloride permeability and good magnesium chloride blocking properties. After the polyamide layer is modified with polyphenol and polyamine, the pore size of the polyamide layer becomes smaller and the surface Zeta potential is further improved, and finally, a separation membrane having a specific pore size and surface Zeta potential defined in the first aspect of the present invention is obtained, and when the separation membrane is used for separating magnesium and lithium, the magnesium-lithium separation efficiency is significantly improved.
[0121] Furthermore, the aqueous phase containing the polyamine and the organic phase containing the polybasic acid chloride are used in amounts such that the mass ratio of polyamine to polybasic acid chloride is 0.5 to 8:1.
[0122] In the present invention, the organic solvent in the organic phase containing the polybasic acid chloride may be at least one of n-hexane, dodecane, n-heptane, and alkane-based solvent oils (commercially available Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).
[0123] According to the present invention, the concentration of the aqueous phase containing the polyamine is preferably 0.1 to 10 wt %, more preferably 0.5 to 2.5 wt %.
[0124] According to the present invention, the concentration of the organic phase containing the polybasic acid chloride is 0.01 to 1 wt%, more preferably 0.1 to 0.5 wt%. When there are multiple types of polybasic acid chloride, they may be mixed in any ratio. For example, when the polybasic acid chloride is trimesoyl chloride and terephthaloyl chloride, the mass ratio of trimesoyl chloride to terephthaloyl chloride may be 1:1 to 10.
[0125] In the present invention, when the concentrations of the aqueous phase containing a polyamine and the organic phase containing a polybasic acid chloride, the contact time between the porous support layer and the aqueous phase containing a polyamine and the organic phase containing a polybasic acid chloride, and the mass ratio of the polyamine to the polybasic acid chloride satisfy the above-mentioned ranges, the thickness of the produced polyamide layer is within the range of 10 to 500 nm.
[0126] In the present invention, when the concentrations of the aqueous phase containing a polyamine and the organic phase containing a polybasic acid chloride satisfy the ranges defined in the present invention, the rejection rate for magnesium ions is improved and the permeability of monovalent lithium ions is improved.
[0127] In the present invention, the volume of the aqueous phase containing the polyamine and the volume of the organic phase containing the polybasic acid chloride are not particularly limited. As long as the amount of the polyamine in the aqueous phase or the amount of the polybasic acid chloride in the organic phase can be secured, a suitable polyamide layer having a crosslinked structure can be formed on the membrane. Preferably, the volume is within 400 cm. 2 For this membrane area, the total amount of polyamine in the aqueous phase may be 0.05 to 2 g, and the total amount of polybasic acid chloride in the organic phase may be 0.0001 to 0.5 g.
[0128] According to the present invention, the polyamine is at least one selected from polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine, more preferably at least one of polyethyleneimine, piperazine, and polyethylenepolyamine.
[0129] According to the present invention, the polybasic acid chloride is at least one selected from trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride, more preferably at least one of trimesoyl chloride and terephthaloyl chloride.
[0130] According to the present invention, the temperature of the heat treatment is 40 to 150° C., and the time of the heat treatment is 0.5 to 10 minutes.
[0131] In the present invention, the polyamine and the polybasic acid chloride react when they come into contact with each other. If the above-mentioned heat treatment conditions are satisfied, the reaction proceeds more completely, and a denser polyamide layer is obtained. After a modification layer is formed on the surface of this polyamide layer, a separation membrane having a specific pore size as described in the first aspect of the present invention is obtained.
[0132] Furthermore, the temperature of the heat treatment is 50 to 120° C., and the time of the heat treatment is 1 to 5 minutes.
[0133] In the present invention, the method further includes the step of immersing the produced separation membrane in deionized water to prepare it for use.
[0134] In a third aspect, the present invention provides a separation membrane produced by the above method.
[0135] In a fourth aspect, the present invention provides the use of a separation membrane according to the first or third aspect in the separation of magnesium and lithium, in particular in the extraction of lithium from salt lakes.
[0136] In the present invention, a specific method of using the separation membrane for separating magnesium and lithium includes the steps of: putting saltwater from a salt lake into a supply tank and mounting the separation membrane on a membrane cell; operating the system at pressure I and collecting the primary wastewater filtered by the separation membrane; putting the primary wastewater into the supply tank as a feed liquid, operating the system at pressure II and collecting the secondary wastewater filtered by the separation membrane.
[0137] In the present invention, the salt water of the salt lake has a magnesium ion content of 500 ppm or more and a lithium ion content of 50 ppm or less.
[0138] In the present invention, Mg in the salt water of the salt lake 2+ and Li +The mass concentration ratio of
[0139] In the present invention, the pressure I is 0.5 to 2 MPa.
[0140] In the present invention, the pressure II is from 0.5 to 2 MPa.
[0141] In the present invention, the primary wastewater has a magnesium ion content of 20 ppm or less and a lithium ion content of 20 ppm or more.
[0142] In the present invention, Mg in the primary wastewater is 2+ and Li + The mass concentration ratio of
[0143] In the present invention, the secondary effluent has a magnesium ion content of 0.5 ppm or less and a lithium ion content of 25 ppm or more.
[0144] In the present invention, the Li in the secondary wastewater is + The purity of is 98% or more.
[0145] In a preferred embodiment of the present invention, the separation membrane has a water permeability of 20 L m when used for separating magnesium and lithium. -2 h -1 The MgCl2 rejection rate is 99% or more, and the magnesium-lithium separation factor is 70 or more.
[0146] Furthermore, the separation membrane has a water permeability of 20 to 40 L m -2 h -1 The MgCl2 rejection rate is 99% or more, and the magnesium-lithium separation factor is 100-250.
[0147] In a particularly preferred embodiment according to the present invention, the separation membrane is produced by the following method.
[0148] A polysulfone solution with a polysulfone concentration of 16 to 19% by weight is applied with a knife onto a polyester nonwoven fabric (base layer) with a thickness of 75 to 80 μm. Next, the material is immersed in water at a temperature of 24 to 26°C for 45 to 60 minutes to cause a phase transition of the polysulfone layer on the surface of the polyester nonwoven fabric to form a porous membrane. Finally, a material including a base layer and a porous support layer (the thickness of the porous support layer is approximately 38 to 42 μm) is obtained by rinsing with water two or three times.
[0149] The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution containing 0.5-0.6 wt% polyethyleneimine at 24-26°C for 50-60s, and the liquid was then drained. The upper surface of the support layer was then contacted with an Isopar E solution containing trimesoyl chloride and terephthaloyl chloride (the mass ratio of the polyamine in the aqueous phase containing the polyamine to the polybasic acid chloride in the organic phase containing the polybasic acid chloride is 5-6:1, and the mass ratio of trimesoyl chloride to terephthaloyl chloride is 1:3-5) at 24-26°C for 60-70s, and the liquid was then drained. The membrane was then placed in an oven and heated at 60-70°C for 3-4min to obtain a material including the base layer, the porous support layer, and the polyamide layer.
[0150] A material including a substrate layer, a porous support layer, and a polyamide layer was placed in a crossflow membrane cell, and the polyamide layer side of the material was brought into contact with a 0.001-0.005 wt % aqueous polyphenol solution in the crossflow membrane cell. The crossflow membrane cell was operated for 30-35 min under conditions of 0.6-0.65 MPa, 25-26°C, and a polyphenol solution flow rate of 2.5-3.5 L / min, after which the liquid was discharged and the crossflow membrane cell was repeatedly rinsed with deionized water to wash away the polyphenols in the system. A polyamine aqueous solution (polyphenol solution and polyamine solution are used in such an amount that the mass ratio of polyphenol to polyamine is 0.1-10:1) is added to the cross-flow membrane cell, and the polyamide layer side of the material is brought into contact with the above solution. The cross-flow membrane cell is operated for 30-35 minutes under conditions of 0.6-0.65 MPa, 25-26°C, and a flow rate of the polyamine solution of 0.5-5 L / min, after which the liquid is discharged and the cross-flow membrane cell is repeatedly rinsed with deionized water to wash off the residual polyamine. In this way, one self-assembly reaction is completed, and the above operation is repeated to complete another self-assembly reaction. A separation membrane is obtained.
[0151] In the present invention, the pressure refers to a gauge pressure.
[0152] The present invention will be described in detail below with reference to examples.
[0153] Isopar E is a commercially available alkane-based solvent oil (purchased from Seiro Chemical Industry Co., Ltd.).
[0154] In the following examples, when the material including the substrate layer, the porous support layer, and the polyamide layer is contacted with the solution in the cross-flow membrane cell, water is circulated into the cross-flow membrane cell by a water pump to maintain the polyphenol solution and polyamine solution in the membrane cell in a flowing state.
[0155] In the other examples and comparative examples except for Examples 11 and 12, materials including a base layer and a porous support layer are produced by the following method.
[0156] Polysulfone (number average molecular weight 80,000 g / mol) is dissolved in N,N-dimethylformamide to obtain a polysulfone solution with a concentration of 18 wt%, which is then degassed at 25°C for 120 min. The polysulfone solution is then applied to a polyester nonwoven fabric (base layer) with a thickness of 75 μm with a knife, and the material is then immersed in water at a temperature of 25°C for 60 min to cause a phase transition of the polysulfone layer on the surface of the polyester nonwoven fabric to form a porous membrane. Finally, it is washed with water three times, and the total thickness including the base layer and the porous support layer (the thickness of the porous support layer is 40 μm) is 115 μm, and the area is 400 cm. 2 Obtain materials.
[0157] For the membranes produced in the following examples and comparative examples, after the membranes are produced, they are immersed in deionized water for 24 hours, and then various properties and parameters are measured.
[0158] The molecular structure of the separation membrane is characterized and analyzed by a total reflection infrared spectrometer (Nicolet 6700).
[0159] The pore size of the separation membrane was measured by PEG solute migration method, the detailed steps of which are as follows:
[0160] (1) Test the rejection rate of the separation membrane against PEG of various molecular sizes.
[0161] (2) Linear fitting is performed on the PEG size and rejection rate in a log-probability coordinate system, and the PEG size corresponding to 50% rejection rate is determined as the average pore size of the separation membrane.
[0162] Surface Zeta potential of the separation membrane: Measured by a Zeta potential analyzer, and the test liquid was a 0.001 mol / L KCl aqueous solution (pH 7).
[0163] Nitrogen atom content in the modification layer of the separation membrane: Measured by X-ray photoelectron spectroscopy (XPS). Obtained by irradiating Al-Kα X-rays in an ESCALAB250 type X-ray photoelectron spectrometer.
[0164] Content of polyphenol-derived structural units and polyamine-derived structural units on the membrane surface of the separation membrane: The membrane including the substrate layer, the porous support layer, and the polyamide layer was dried in a vacuum oven at 60° C. for 24 hours, and then the mass of the membrane was weighed. n The membrane is placed in a membrane cell, a polyphenol aqueous solution of a predetermined concentration is placed in the supply tank, and cycled for a certain period of time under predetermined conditions. The membrane sheet is then removed, the surface of the membrane sheet is thoroughly washed with deionized water, and dried at 60°C for 24 hours. The mass of the membrane is then weighed and the mass is expressed as W n Next, the membrane is placed in a membrane cell, a polyamine aqueous solution of a specified concentration is added to the supply tank, and cycled for a certain period of time under specified conditions. The membrane sheet is then taken out, the surface of the membrane sheet is thoroughly washed with deionized water, and dried at 60°C for 24 h. The mass of the membrane is then weighed and N n (mg). Each time the separation membrane was modified, the polyphenol content on the membrane surface, P n and polyamine content T n are calculated by the following formulas, respectively:
number
[0165] Here, if n is greater than 1, then M n =N n-1 and for n=1, M n is the initial mass of the polyamide membrane sheet.
number
[0166] The total content of polyphenols on the surface of the separation membrane after self-assembly is ΣPn (n ≧ 1), and the total content of polyamines on the surface is ΣTn (n ≧ 1). where n is the number of self-assembly times and S is the effective membrane area (unit: cm 2 ).
[0167] Here, the conditions for contacting the membrane with the aqueous solution of polyphenols and the aqueous solution of polyamines correspond to the first pressure, the second pressure, the temperature and time of the first contact, and the temperature and time of the second contact in the self-assembly process in the examples and comparative examples, respectively.
[0168] Contact angle of separation membrane: Using a DSA100 surface contact angle measuring device manufactured by KRUSS, Germany, the surface contact angle of the composite membrane sample is measured using the sessile drop method. Before the measurement, the sample is dried in a vacuum oven at 60°C for 30 min to remove the moisture on its surface and inside, and then the dried membrane is attached to a flat glass slide with double-sided tape, the volume of each water drop during the test is 2 μL, and the test is performed immediately 3 s after the water drop is dropped on the surface of the membrane, and the average value of multiple measurements is obtained to determine the final contact angle.
[0169] The thickness of the separation membrane and each layer of the separation membrane: the thickness of the separation membrane, the porous support layer, and the polyamide layer are measured by a spiral micrometer and a scanning electron microscope, and the thickness of the modification layer is obtained by subtracting the thickness of the substrate layer, the porous support layer, and the polyamide layer from the thickness of the separation membrane, where the thickness of the substrate layer is the thickness measured before applying the solution of the material of the porous support layer.
[0170] Example 1 The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution (50 mL) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, after which the liquid was drained off. The top surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.02 wt% trimesoyl chloride and 0.08 wt% terephthaloyl chloride at 25°C for an additional 60 s, after which the liquid was drained off. The membrane was then placed in an oven and heated at 70°C for 3 min. The heat-treated product was placed in a cross-flow membrane cell, and the first contact between the polyamide layer side of the material and the 0.001wt% tannic acid aqueous solution in the cross-flow membrane cell was carried out, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was kept in a flowing state, the flow rate was 1.5L / min, and the cross-flow membrane cell was operated at 0.6MPa and 25°C for 30min, after which the liquid was discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the tannic acid in the system. 5L of a polyethyleneimine aqueous solution with a concentration of 0.004wt% was added to the cross-flow membrane cell, and the polyethyleneimine aqueous solution was kept in a flowing state, the flow rate was 1.5L / min, and the second contact between the polyamide layer side of the material and the above solution was carried out, and the cross-flow membrane cell was operated at 0.6MPa and 25°C for 30min, after which the liquid was discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the residual polyethyleneimine. In this way, one self-assembly reaction was completed, and the above operation was repeated to complete another self-assembly reaction. In one self-assembly, the mass ratio of polyphenol to polyamine was 0.25:1. Thus, separation membrane N1 was obtained.
[0171] Example 2 The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution (50 mL) containing 1 wt% polyethylene polyamine at 25°C for 20 s, after which the liquid was drained off. The top surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.18 wt% trimesoyl chloride and 0.12 wt% terephthaloyl chloride at 25°C for an additional 30 s, after which the liquid was drained off. The membrane was then placed in an oven and heated at 50°C for 5 min. The heat-treated product was placed in a cross-flow membrane cell, and the first contact between the polyamide layer side of the material and the 0.01 wt% tannic acid aqueous solution in the cross-flow membrane cell was performed, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was kept in a flowing state, the flow rate was 0.5L / min, and the cross-flow membrane cell was operated at 0.6MPa and 15°C for 40min, after which the liquid was discharged, and the solution in the cross-flow membrane cell was repeatedly rinsed with deionized water to wash out the residual tannic acid. 5L of polyethyleneimine aqueous solution with a concentration of 0.045wt% was added to the cross-flow membrane cell, and the polyethyleneimine aqueous solution was kept in a flowing state, the flow rate was 0.5L / min, and the second contact between the polyamide layer side of the material and the above solution was performed, and the cross-flow membrane cell was operated at 0.6MPa and 15°C for 40min, after which the liquid was discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash out the residual polyethyleneimine. In this way, one self-assembly reaction was completed, and the above operations were repeated to complete another self-assembly reaction. In one self-assembly, the mass ratio of polyphenol to polyamine was 0.22:1. Thus, separation membrane N2 was obtained.
[0172] Example 3 The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution (50 mL) containing 2.5 wt % piperazine at 25° C. for 40 s, after which the liquid was drained off. The top surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.2 wt % trimesoyl chloride and 0.1 wt % terephthaloyl chloride at 25° C. for an additional 100 s, after which the liquid was drained off. The membrane was then placed in an oven and heated at 110° C. for 1 min. The heat-treated product was placed in a cross-flow membrane cell, and the first contact between the polyamide layer side of the material and the 0.1 wt% tannic acid aqueous solution in the cross-flow membrane cell was performed, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was kept in a flowing state, the flow rate was 5L / min, and the cross-flow membrane cell was operated at 0.6MPa and 30°C for 20min, after which the liquid was discharged and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash off the residual tannic acid. 5L of a 0.1 wt% aqueous polyethyleneimine solution was added to the cross-flow membrane cell, the polyethyleneimine aqueous solution was kept in a flowing state, the flow rate was 5L / min, and the second contact between the polyamide layer side of the material and the above solution was performed, and the cross-flow membrane cell was operated at 0.6MPa and 30°C for 20min, after which the liquid was discharged and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash off the residual polyethyleneimine. In this way, one self-assembly reaction was completed, and the above operation was repeated to complete another self-assembly reaction. In one self-assembly, the mass ratio of polyphenol to polyamine was 1:1. Thus, separation membrane N3 was obtained.
[0173] Example 4 A separation membrane was produced according to the method of Example 1, except that in the self-assembly reaction, polyethyleneimine was changed to polyethylenepolyamine. Separation membrane N4 was obtained.
[0174] Example 5 A separation membrane was produced according to the method of Example 1, except that in the self-assembly reaction, polyethyleneimine was changed to tetraethylenepentamine. Separation membrane N5 was obtained.
[0175] Example 6 A separation membrane was produced according to the method of Example 1, except that in the self-assembly reaction, polyethyleneimine was changed to triethylenetetramine. Separation membrane N6 was obtained.
[0176] Example 7 A separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was carried out only once. Separation membrane N7 was obtained.
[0177] Example 8 A separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was performed a total of three times. Separation membrane N8 was obtained.
[0178] Example 9 A separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was performed a total of four times. Separation membrane N9 was obtained.
[0179] Example 10 A separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was performed a total of 5 times. Separation membrane N10 was obtained.
[0180] Example 11 A separation membrane was manufactured according to the method of Example 1, except that the material including the substrate layer and the porous support layer was manufactured by the following method. Polyethersulfone (number average molecular weight 70,000 g / mol) was dissolved in N,N-dimethylformamide to obtain a polyethersulfone solution with a concentration of 20 wt%, and the solution was degassed at 25°C for 120 min. The polyethersulfone solution was then applied to a polyethylene nonwoven fabric (substrate layer) with a thickness of 100 μm with a knife, and the material was then immersed in water at a temperature of 23°C for 20 min to cause a phase transition of the polyethersulfone layer on the surface of the polyethylene nonwoven fabric to form a porous membrane. Finally, the membrane was washed with water three times to obtain a membrane with a total thickness of 135 μm including the substrate layer and the porous support layer (the porous support layer is 35 μm thick) and an area of 400 cm. 2 The material was obtained. Separation membrane N11 was obtained.
[0181] Example 12 A separation membrane was manufactured according to the method of Example 1, except that the material including the substrate layer and the porous support layer was manufactured by the following method. Polyacrylonitrile (number average molecular weight 100,000 g / mol) was dissolved in N,N-dimethylformamide to obtain a polyacrylonitrile solution with a concentration of 15 wt%, and degassed at 25°C for 120 min. The polyacrylonitrile solution was then applied to a polypropylene nonwoven fabric (substrate layer) with a thickness of 115 μm with a knife, and the material was then immersed in water at a temperature of 28°C for 40 min to cause a phase transition of the polyacrylonitrile layer on the surface of the polypropylene nonwoven fabric to form a porous membrane. Finally, it was washed with water three times, and a total thickness of 160 μm including the substrate layer and the porous support layer (the porous support layer is 45 μm thick) and an area of 400 cm were obtained. 2 The material was obtained. Separation membrane N12 was obtained.
[0182] Example 13 In the self-assembly reaction, the concentration of tannic acid in the tannic acid aqueous solution is 0.0001wt%, the concentration of polyethyleneimine in the polyethyleneimine solution is 0.001wt%, and in each self-assembly, the mass ratio of polyphenol to polyamine is 0.1:1. Separation membrane N13 is obtained.
[0183] Example 14 The separation membrane was prepared according to the method of Example 1, except that the first and second pressures in the self-assembly were both 0.2 MPa, and the flow rates of the solutions were all 1.5 L / min. Separation membrane N14 was obtained.
[0184] Example 15 A separation membrane was prepared according to the method of Example 1, except that the pressure of the first contact and the second contact in the self-assembly was 1 MPa, and the flow rates of the solutions were all 1.5 L / min. Separation membrane N15 was obtained.
[0185] Example 16 A separation membrane was prepared according to the method of Example 1, except that the pressure of the first contact and the second contact in the self-assembly was 0.8 MPa, and the flow rates of the solutions were all 1.5 L / min. Separation membrane N16 was obtained.
[0186] Example 17 A separation membrane was prepared according to the method of Example 1, except that the pressure of the first contact and the second contact in the self-assembly was 0.4 MPa, and the flow rates of the solutions were all 1.5 L / min. Separation membrane N17 was obtained.
[0187] Example 18 The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution (50 mL) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, after which the liquid was drained off. The top surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.01 wt% trimesoyl chloride and 0.04 wt% terephthaloyl chloride at 25°C for an additional 60 s, after which the liquid was drained off. The membrane was then placed in an oven and heated at 70°C for 3 min. The heat-treated product was placed in a cross-flow membrane cell, and the first contact between the polyamide layer side of the material and the 0.001wt% tannic acid aqueous solution in the cross-flow membrane cell was carried out, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was kept in a flowing state, the flow rate was 1.5L / min, and the cross-flow membrane cell was operated at 0.6MPa and 25°C for 30min, after which the liquid was discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the tannic acid in the system. 5L of a polyethyleneimine aqueous solution with a concentration of 0.004wt% was added to the cross-flow membrane cell, and the polyethyleneimine aqueous solution was kept in a flowing state, the flow rate was 1.5L / min, and the second contact between the polyamide layer side of the material and the above solution was carried out, and the cross-flow membrane cell was operated at 0.6MPa and 25°C for 30min, after which the liquid was discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the residual polyethyleneimine. In this way, one self-assembly reaction was completed, and the above operation was repeated to complete another self-assembly reaction. In one self-assembly, the mass ratio of polyphenol to polyamine was 0.25:1. Thus, separation membrane N18 was obtained.
[0188] Example 19 In the self-assembly reaction, the concentration of tannic acid in the tannic acid aqueous solution is 0.001wt%, the concentration of polyethyleneimine in the polyethyleneimine solution is 0.0001wt%, and in each self-assembly, the mass ratio of polyphenol to polyamine is 10:1. Separation membrane N19 is obtained.
[0189] Comparative Example 1 A separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was not performed, that is, the separation membrane was obtained by heat treatment. Separation membrane D1 was obtained.
[0190] Comparative Example 2 The product after heat treatment was put into a cross-flow membrane cell containing 0.001wt% tannic acid aqueous solution, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was kept in a flowing state, the flow rate was 1.5L / min, and the cell was operated at 0.6MPa and 25℃ for 30min. Then, the product was taken out to obtain a separation membrane (i.e., contacted with the tannic acid aqueous solution only once), and the separation membrane was prepared according to the method of Example 1. Separation membrane D2 was obtained.
[0191] Comparative Example 3 A separation membrane was produced according to the method of Example 1, except that polyethyleneimine was changed to polyvinyl alcohol. Separation membrane D3 was obtained.
[0192] Comparative Example 4 The polyacrylonitrile ultrafiltration membrane was placed in a cross-flow membrane cell so that one side was in contact with a 0.001 wt% tannic acid aqueous solution in the cross-flow membrane cell, the volume of the tannic acid aqueous solution was 5L, the tannic acid solution was maintained in a flowing state, the flow rate was 1.5L / min, the cross-flow membrane cell was operated at 0.6 MPa and 25°C for 30 min, the liquid was then discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the tannic acid in the system. 5L of a polyethyleneimine aqueous solution with a concentration of 0.004 wt% was added to the cross-flow membrane cell, the polyacrylonitrile layer side of the material was contacted with the above solution, the flow rate was 1.5L / min, the cross-flow membrane cell was operated at 0.6 MPa and 25°C for 30 min, the liquid was then discharged, and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the remaining polyethyleneimine. In this way, one self-assembly reaction was completed, and the above operations were repeated to complete another self-assembly reaction. In one self-assembly, the mass ratio of polyphenol to polyamine was 0.25:1, thereby obtaining separation membrane D4.
[0193] Comparative Example 5 The porous support layer of the material including the base layer and the porous support layer was placed in a cross-flow membrane cell, and one side of the porous support layer was first contacted with a 0.001 wt% aqueous tannic acid solution in the cross-flow membrane cell, the volume of the aqueous tannic acid solution was 5 L, the tannic acid solution was maintained in a flowing state with a flow rate of 1.5 L / min, and the cross-flow membrane cell was operated at 0.6 MPa and 25°C for 30 min, after which the liquid was discharged and the cross-flow membrane cell was repeatedly rinsed with deionized water to wash the tannic acid in the system. Add 5L of polyethyleneimine aqueous solution with a concentration of 0.004wt% to the cross-flow membrane cell, maintain the polyethyleneimine aqueous solution in a flowing state, and set the flow rate to 1.5L / min to perform a second contact between the polyacrylonitrile layer side of the material and the above solution. After operating the cross-flow membrane cell at 0.6MPa and 25°C for 30min, drain the liquid, take out the membrane sheet, and rinse the surface thoroughly with deionized water to obtain a porous support layer modified with polyphenol and polyamine; the mass ratio of polyphenol to polyamine in one self-assembly is 0.25:1; The surface of the porous support layer modified with polyphenol and polyamine was contacted with an aqueous solution (50 mL) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, and the liquid was then drained. The upper surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.02 wt% trimesoyl chloride and 0.08 wt% terephthaloyl chloride at 25°C for another 60 s, and the liquid was then drained. The membrane was then placed in an oven and heated at 70°C for 3 min to prepare a separation membrane according to the method of Example 1, except that a polyamide composite membrane D5 with an intermediate layer of polyamine and polyphenol was obtained.
[0194] Comparative Example 6 Instead of putting the heat-treated product into a cross-flow membrane cell to carry out the self-assembly reaction, the polyamide layer side of the material was contacted with a tannic acid aqueous solution (i.e., the first pressure was 0 MPa, and the tannic acid solution did not flow) in a beaker containing a tannic acid aqueous solution, and after 24 hours, the material was removed and repeatedly rinsed with deionized water; then, the polyamide layer side of the material was contacted with a polyethyleneimine aqueous solution (i.e., the second pressure was 0 MPa, and the polyethyleneimine solution did not flow) in a beaker containing a polyethyleneimine aqueous solution, and after 24 hours, the material was removed and repeatedly rinsed with deionized water; by repeating the above operations, another self-assembly reaction was completed, and a separation membrane was obtained. A separation membrane was produced according to the method of Example 1. Here, in each self-assembly, the volume of the tannic acid solution (or polyamine) in the beaker was made to exceed the amount that the total amount of tannic acid (or polyamine) could adhere to and react on the membrane. Separation membrane D6 was obtained.
[0195] Comparative Example 7 The surface of the porous support layer of the material including the base layer and the porous support layer was contacted with an aqueous solution (50 mL) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, after which the liquid was drained off. The top surface of the support layer was then contacted with an Isopar E solution (30 mL) containing 0.02 wt% trimesoyl chloride and 0.08 wt% terephthaloyl chloride at 25°C for an additional 60 s, after which the liquid was drained off. The membrane was then placed in an oven and heated at 70°C for 3 min. The obtained membrane was immersed in 1 L of a tannic acid aqueous solution with a concentration of 2 wt% (the first pressure was 0 MPa, and the tannic acid solution did not flow) for 1 min, and after removal, the surface of the membrane was washed with deionized water. Next, the membrane was immersed in 1 L of a polyethyleneimine aqueous solution with a concentration of 2 wt% (the second pressure was 0 MPa, and the polyethyleneimine solution did not flow) for 1 min. In one self-assembly, the mass ratio of polyphenols to polyamines was 1:1. After removal of the membrane, the membrane surface was thoroughly rinsed with deionized water to obtain separation membrane D7.
[0196] Comparative Example 8 A separation membrane was prepared according to the method of Example 1, except that the first and second pressures in the self-assembly were both 0 MPa, and the flow rates of the solutions were all 1.5 L / min. Separation membrane D8 was obtained.
[0197] Comparative Example 9 A separation membrane was produced according to the method of Example 1, except that the polyamide membrane was first contacted with a polyethyleneimine solution and then with a tannic acid solution, and the self-assembly was carried out only once. Separation membrane D9 was obtained.
[0198] The separation membranes produced in Example 1 and Comparative Examples 1 and 2 were subjected to infrared spectrum characteristic evaluation, and the results are shown in FIG.
[0199] The membrane not modified by self-assembly of tannic acid and polyethyleneimine (membrane of Comparative Example 1) had a peak at 3388 cm -1 There is one broad peak at 1507 cm, which corresponds to unreacted amines on the surface of the polyamide, and another broad peak at 1511 cm -1A weak signal was observed at 3364 cm, which corresponds to the stretching vibration of NH. -1 There is a strong absorption peak at 1507 cm, which corresponds to the phenolic hydroxyl group in the tannic acid molecule, and -1 The signal peak at 3270 to 3390 cm almost disappeared, which confirms that the amino and tannic acid have undergone a chemical reaction. In the film in Example 1 in which tannic acid and polyethyleneimine have undergone self-assembly twice in succession on the surface of the polyamide, the signal peak at 3270 to 3390 cm -1 There is one broad peak at 1507 cm, which corresponds to the unreacted amino and unreacted phenolic hydroxyl groups on the modified layer, and another broad peak at 1517 cm. -1 The signal at is enhanced, which confirms that polyethyleneimine has been modified on the surface of the membrane. Referring to the operation and infrared image of Comparative Example 2, it was found that in the separation membrane of Example 1, the crosslinked polymer forming the modified layer contains a structural unit derived from tannic acid and a structural unit derived from polyamine, and the structural unit derived from tannic acid is also connected to the polyamide layer through the ortho position of the phenolic hydroxyl group. The infrared characteristic evaluation results of the separators prepared in Examples 2 to 19 are similar to those of Example 1 (not shown).
[0200] [Table 1]
[0201] [Table 2]
[0202] As can be seen from Tables 1 and 2, compared with Comparative Examples 1 to 9, the separation membranes of Examples 1 to 19 have smaller pore sizes and the modified layer has a high positive charge density.
[0203] In Comparative Example 2, the thickness of the modified layer is the change in thickness due to tannic acid, and in Comparative Example 3, the thickness of the modified layer is the change in thickness due to the reaction of tannic acid and polyvinyl alcohol.
[0204] Furthermore, the separation membrane according to the present invention has a small pore size and a high surface Zeta potential, and when used for separating magnesium and lithium, the rejection rate of magnesium chloride is significantly improved. In addition, the separation membrane has excellent hydrophilicity and can achieve excellent water permeability.
[0205] As can be seen from Figure 2, as the number of self-assembly increases, the potential of the membrane surface tends to be positively charged and its absolute value increases. It was found that as the number of self-assembly increases, the content of amino (primary amine, secondary amine, or tertiary amine) on the membrane surface increases, thereby improving the Zeta potential of the membrane surface.
[0206] As can be seen from FIG. 3, as the self-assembly pressure (i.e., first pressure / second pressure) increased during self-assembly, the absolute value of the positive potential on the membrane surface increased, which indicated that pressure was favorable for reacting high contents of polyphenols and polyamines on the membrane surface.
[0207] As can be seen from FIG. 4, as the self-assembly pressure (i.e., first pressure / second pressure) increases during self-assembly, the content of hydrophilic primary amine groups, secondary amine groups, or tertiary amine groups on the membrane surface increases, thereby improving the hydrophilicity of the membrane surface.
[0208] As can be seen from FIG. 5, as the number of self-assembly increases, the content of hydrophilic primary amine groups, secondary amine groups, or tertiary amine groups on the membrane surface increases, thereby improving the hydrophilicity of the membrane surface.
[0209] As can be seen from Fig. 6a, the polyamide layer not modified with polyphenols and polyamines is smooth and thin, with a thickness of 85 nm, and as can be seen from Fig. 6b, when the self-assembly modification is performed on the surface of the polyamide layer using polyphenols and polyamines, the surface of the polyamide layer becomes covered with a modification layer with a thickness of about 30 nm.
[0210] FIG. 7 compares the XPS nitrogen element maps of Example 1 (FIG. 7a) and Comparative Example 6 (FIG. 7b). As can be seen from this figure, the modified layer of Example 1 has one characteristic peak at 407 eV, which corresponds to the structural unit shown in Formula I, i.e., a π-π bond formed by a benzene ring-nitrogen atom-benzene ring. * This is a signal peak due to electronic conjugation. On the other hand, in Comparative Example 6, this signal peak was not observed, which indicated that the structural unit represented by formula I could only be produced under the process conditions of the present invention, such as the pressure driving self-assembly. One nitrogen atom and two benzene rings in this structural unit undergo a cross-linking reaction, thereby improving the density of the separation membrane and reducing the pore size of the separation membrane.
[0211] Application Examples Each of the separation membranes manufactured in the Examples and Comparative Examples was placed in a crossflow membrane cell, and the water permeation rate of the separation membrane was increased for a certain period of time under conditions of 0.6 MPa and 25°C. The water permeation rate was calculated according to the following formula. J = Q / (A t) where J is the water throughput (L / m 2 h), Q is the water permeation rate (L), and A is the effective membrane area of the separation membrane (m 2 ) and t is time (h). The separation membrane was placed in a cross-flow membrane cell. The feed liquid in the membrane cell contained 2000 ppm magnesium chloride or 2000 ppm lithium chloride. After pre-compression at 0.2 MPa for 0.5 hours, a permeate was obtained at a pressure of 0.6 MPa and a feed liquid temperature of 25°C. The concentrations of magnesium chloride and lithium chloride in the permeate were measured using a conductivity meter, and the salt rejection rate was calculated using the following formula. R(%)=(C f -C P ) / C f ×100% where R is the salt rejection rate and C f is the concentration of magnesium chloride or lithium chloride in the raw liquid (measured with a conductivity meter), and C pis the concentration of magnesium chloride or lithium chloride in the permeate (measured by a conductivity meter). The separation membrane was placed in a cross-flow membrane cell. The feed liquid in the membrane cell contained 2000 ppm magnesium chloride and 100 ppm lithium chloride. After pre-compression at 0.2 MPa for 0.5 h, a permeate was obtained at a pressure of 0.6 MPa and a temperature of the feed liquid of 25°C. The concentrations of magnesium ions and lithium ions in the permeate were measured by ion chromatography. The magnesium-lithium separation factor was calculated by the following formula:
number
[0212] [Table 3]
[0213] As can be seen from Table 3, according to the embodiment of the technical solution of the present invention, it is possible to achieve both a large water passing rate and a high magnesium-lithium separation efficiency. As the number of self-assembly increases, the content of polyphenols and polyamines on the membrane surface is improved, thereby improving the hydrophilicity of the membrane surface and the surface Zeta potential. As a result, the rejection rate of the membrane for magnesium chloride is improved, and the magnesium-lithium separation coefficient is improved. Meanwhile, as the number of self-assembly increases, the thickness of the modification layer increases, thereby reducing the water passing rate of the membrane. Furthermore, as the operating pressure in the self-assembly increases, the reaction is more efficient, and the hydrophilicity of the membrane surface and the surface Zeta potential are improved, so that the membrane has an improved salt rejection rate and magnesium-lithium separation efficiency.
[0214] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, the technical solution of the present invention may be modified in a number of simple ways, including combining each technical feature in any other suitable manner, and these simple modifications and combinations should also be regarded as the disclosure of the present invention, and all belong to the protection scope of the present invention.
[0215] [Explanation of symbols] 1 modification layer 2 polyamide layers 3 Porous support layer [Brief description of the drawings]
[0216] [Figure 1] 3 shows infrared spectra of the separation membranes produced in Example 1 and Comparative Examples 1 and 2 of the present invention. [Diagram 2] 1 is a curve showing the change in surface Zeta potential of a separation membrane with the number of self-assembly cycles. [Diagram 3] 1 is a curve showing the change in surface Zeta potential of a separation membrane with the self-assembly pressure (first pressure / second pressure). [Figure 4] 1 is a curve showing the change in contact angle of a separation membrane with the self-assembly pressure (first pressure / second pressure). [Diagram 5] 1 is a curve showing the change in contact angle of a separation membrane depending on the number of times of self-assembly. [Figure 6a] 6A and 6B are cross-sectional SEM images of the separation membranes of Comparative Example 1 (FIG. 6A) and Example 10 (FIG. 6B). [Figure 6b] 6A and 6B are cross-sectional SEM images of the separation membranes of Comparative Example 1 (FIG. 6A) and Example 10 (FIG. 6B). [Figure 7a] 1 shows XPS nitrogen element maps of the separators prepared in Example 1 and Comparative Example 1. [Figure 7b] 1 shows XPS nitrogen element maps of the separators prepared in Example 1 and Comparative Example 1.
Claims
1. A separation membrane, The substrate includes a substrate layer, a porous support layer, a polyamide layer, and a modification layer, in that order; The crosslinked polymer forming the modification layer comprises structural units derived from polyphenols and structural units derived from polyamines, at least a portion of the structural units derived from polyphenols are also connected to the polyamide layer through the ortho positions of the phenolic hydroxyl groups; A separation membrane having a pore size of 0.1 to 0.5 nm and a surface Zeta potential of -5 mV to 30 mV.
2. 2. The separation membrane according to claim 1, which has a pore size of 0.15 to 0.3 nm and a surface Zeta potential of 1 mV to 10 mV.
3. The separation membrane according to claim 1 or 2, wherein the modified layer comprises a structural unit represented by formula I: 【Chemistry 1】
4. The content of the structural unit derived from the polyphenol on the film surface is 2×10 -3 ~5×10 -2 mg / cm 2 , preferably 2.5×10 -3 ~5×10 -2 mg / cm 2 The content of the structural unit derived from the polyamine on the surface of the film is 1×10 -3 ~2.5 x 10 -2 mg / cm 2 , preferably 4×10 -3 ~2×10 -2 mg / cm 2 The separation membrane according to any one of claims 1 to 3.
5. The separation membrane according to any one of claims 1 to 4, wherein the content of N atoms in the modification layer is 13 to 20 at. %, preferably 13.5 to 18.5 at. %.
6. The separation membrane according to any one of claims 1 to 5, wherein the contact angle is from 20 to 60°, preferably from 20 to 40°.
7. The thickness of the separation membrane is 100 to 200 μm. and / or the thickness of the substrate layer is 30 to 150 μm, preferably 50 to 120 μm; and / or the thickness of the porous support layer is 10 to 100 μm, preferably 30 to 60 μm; and / or the thickness of the polyamide layer is between 10 and 500 nm, preferably between 50 and 150 nm; And / or the thickness of the modification layer is 1 to 200 nm, preferably 10 to 60 nm.
8. the material of the base material layer is at least one selected from a polyester nonwoven fabric, a polyethylene nonwoven fabric, and a polypropylene nonwoven fabric; And / or, the material of the porous support layer is at least one selected from polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryletherketone. The separation membrane according to any one of claims 1 to 7.
9. the polyamide layer is synthesized from a polyamine and a polybasic acid chloride; and / or the polyamine is at least one selected from polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine, preferably at least one selected from polyethyleneimine, piperazine, and polyethylenepolyamine; And / or the polybasic acid chloride is at least one selected from trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride, preferably at least one of trimesoyl chloride and terephthaloyl chloride. The separation membrane according to any one of claims 1 to 8.
10. the modified layer is obtained by a self-assembly reaction of a polyphenol and a polyamine on a polyamide layer; Preferably, the polyphenol is one or more selected from tannic acid, tea polyphenol, gallic acid, catechin, lignin, sodium lignosulfonate, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin, and genistein, preferably tannic acid and / or tea polyphenol; The separation membrane according to any one of claims 1 to 9, wherein the polyamine is at least one selected from the group consisting of polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
11. A method for producing a separation membrane, comprising the steps of: Producing a porous support layer, a polyamide layer, and a modification layer in this order on a substrate layer; The method for producing the modified layer includes first contacting the polyamide layer side of a material including a substrate layer, a porous support layer, and a polyamide layer with the polyphenol solution while flowing the polyphenol solution under a first pressure, and then second contacting the polyamide layer side of the material with the polyamine solution while flowing the polyamine solution under a second pressure, thereby completing a self-assembly reaction.
12. the first pressure and the second pressure are each independently 0.1 to 1.2 MPa, preferably 0.2 to 1 MPa; Preferably, the polyphenol solution and the polyamine solution are used in amounts such that the mass ratio of polyphenol to polyamine is 0.1 to 10:1, preferably 0.2 to 6:1, Preferably, the concentration of the polyphenol solution is 0.00001 to 1 wt %, preferably 0.0001 to 0.1 wt %; The method according to claim 11, wherein the concentration of the polyamine solution is preferably 0.00001-1 wt%, preferably 0.0001-0.1 wt%.
13. the temperature of the first contact and the second contact is each independently from 10 to 30° C.; Preferably, in one self-assembly reaction, the first contact time is 1 to 120 min, preferably 10 to 60 min; Preferably, in one self-assembly reaction, the second contact time is 1 to 120 min, more preferably 10 to 60 min; Preferably, the number of times of the self-assembly reaction is 1 to 10 times, more preferably 2 to 5 times; Preferably, the conditions for producing the modified layer include providing a thickness of the modified layer in the separation membrane of 1 to 200 nm, preferably 10 to 60 nm.
14. The polyphenol in the polyphenol solution is one or more selected from tannic acid, tea polyphenol, gallic acid, catechin, lignin, sodium ligninsulfonate, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin, and genistein, preferably tannic acid and / or tea polyphenol; The method according to any one of claims 11 to 13, wherein the polyamine in the polyamine solution is at least one selected from polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
15. The method for producing the porous support layer comprises the steps of: A step of applying a solution containing a porous support layer material onto a base layer, and performing a phase transition to obtain a material containing a base layer and a porous support layer, Preferably, the phase transition conditions include immersion in water at 10 to 30° C. for 10 to 60 min; Preferably, the thickness of the substrate layer is between 30 and 150 μm, preferably between 50 and 120 μm; Preferably, the material of the base material layer is at least one selected from a polyester nonwoven fabric, a polyethylene nonwoven fabric, and a polypropylene nonwoven fabric, Preferably, the conditions for producing the porous support layer include providing a thickness of the porous support layer in the separation membrane of 10 to 100 μm, more preferably 30 to 60 μm; Preferably, the concentration of the solution containing the porous support layer material is 10 to 20 wt %; Preferably, the porous support layer material is at least one selected from polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryletherketone; The method according to any one of claims 11 to 14, wherein the solvent in the solution containing the porous support layer material is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethylsulfoxide.
16. The method for producing the polyamide layer includes the steps of contacting a surface of a porous support layer of a material including a base layer and a porous support layer with an aqueous phase containing a polyamine and an organic phase containing a polybasic acid chloride in that order, and then performing a heat treatment, Preferably, the conditions for producing the polyamide layer include providing a thickness of the polyamide layer in the separator of 10 to 500 nm, more preferably 50 to 300 nm; Preferably, the time for contacting the surface of the porous support layer with the aqueous phase containing the polyamine is 5 to 100 s, more preferably 10 to 60 s; Preferably, the time for contacting the surface of the porous support layer with the organic phase containing the polybasic acid chloride is 10 to 200 s, more preferably 20 to 120 s; Preferably, the aqueous phase containing the polyamine and the organic phase containing the polybasic acid chloride are used in such amounts that the mass ratio of the polyamine to the polybasic acid chloride is 0.1 to 10:1, preferably 0.5 to 8:1; Preferably, the concentration of the aqueous phase containing the polyamine is 0.1 to 10 wt %, more preferably 0.5 to 2.5 wt %; Preferably, the concentration of the organic phase containing the polybasic acid chloride is 0.01 to 1 wt %, more preferably 0.1 to 0.5 wt %; Preferably, the polyamine is at least one selected from polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine, more preferably at least one of polyethyleneimine, piperazine, and polyethylenepolyamine; Preferably, the polybasic acid chloride is at least one selected from trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride, more preferably at least one of trimesoyl chloride and terephthaloyl chloride; The method according to any one of claims 11 to 15, wherein the temperature of the heat treatment is preferably 40 to 150°C, more preferably 50 to 120°C, and the time of the heat treatment is 0.5 to 10 min, more preferably 1 to 5 min.
17. A separation membrane produced by the method according to any one of claims 11 to 16.
18. Use of the separation membrane according to any one of claims 1 to 10 and claim 17 in separating magnesium and lithium.
Citation Information
Patent Citations
Solidified tannin polyamide microporous membrane and preparation method and application thereof
CN108031450A
Reverse osmosis membrane and preparation method and application thereof
CN109289551A
Nano-filtration membrane, preparation method and applications of thereof
CN109692584A
Composite nanofiltration membrane and preparation method and application thereof
CN110394074A
Composite semipermeable membrane
JP2018187533A